Front blocking versus propagation in the presence of drift term varying in the direction of propagation. (August 2020) - Eberle, Simon
Abstract: In this paper we derive quantitative conditions under which a compactly supported drift term depending on the direction of propagation blocks a traveling wave solution or lets it pass almost unchanged. We give explicit conditions on the drift term for blocking as well as almost unchanged propagation in one spatial dimension.